Ethnic-wise population forecast for Singapore using Lee Carter model for mortality, fertility and migration. - Goh, Siu Wei. (2011)
In this study, we investigate Singapore population using the variant of Lee-Carter model proposed by Hyndman and Ullah. The mortality rates, fertility rates and net migration numbers which form the basis of the population are analysed. Coherent functional forecasting method is adopted to restrict the divergence of forecast mortality rates between male and female. The model is applied on Singapore demographics data from 1982 to 2008 to forecast the population from 2009 to 2029. The accuracy of the estimates is assessed by comparing the forecast result against actual data from year 2001 to 2009. Next, the forecast demographic components (mortality, fertility and net migration) between Chinese, Malay and Indian are compared and discussed. Possible evolution in ethnic population trend within Singapore is then justified. The results show that there is an upward trend in Singapore population between years 2009 to 2029. Ethnic-wise forecasts show that Indian population will outnumber Malay population by 2021. There is also increasing proportion of elderly population within the forecast periods. Finally, limitations of the model are discussed and concluding remarks are made at the end of the report with recommendations on possible future research.